1989
DOI: 10.1164/ajrccm/139.4.1042
|View full text |Cite
|
Sign up to set email alerts
|

Does Aluminum Smelting Cause Lung Disease?

Abstract: The evidence concerning a relationship between work in the aluminum industry and lung disease has been reviewed using epidemiologic criteria. Adequate data on environmental exposure are rarely presented. Case series on aluminum potroom workers over the past 50 years have identified an asthmalike syndrome that appears to be due to an irritant rather than an allergic mechanism. These studies have been supported by evidence of within shift variability of measures of lung function. However, to date, there is inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 11 publications
4
67
1
1
Order By: Relevance
“…The controls consisted of 15 healthy potroom workers (eight nonsmokers and seven smokers) and 10 healthy, nonexposed subjects (all nonsmokers). The diagnosis of occupational asthma was set by confirming the diagnosis of bronchial asthma according to international guidelines [9] and by establishing a causal link between asthma and the working environment, in line with previously defined criteria for occupational asthma in the aluminium industry [10]. Serial monitoring of peak expiratory flow was performed both at work and away from work.…”
Section: Subjectsmentioning
confidence: 99%
“…The controls consisted of 15 healthy potroom workers (eight nonsmokers and seven smokers) and 10 healthy, nonexposed subjects (all nonsmokers). The diagnosis of occupational asthma was set by confirming the diagnosis of bronchial asthma according to international guidelines [9] and by establishing a causal link between asthma and the working environment, in line with previously defined criteria for occupational asthma in the aluminium industry [10]. Serial monitoring of peak expiratory flow was performed both at work and away from work.…”
Section: Subjectsmentioning
confidence: 99%
“…Several morbidity studies have found associations between potroom work and obstructive lung disease, while some cross-sectional morbidity studies have not been able to detect any work-related respiratory effect (18). However, workers leaving or changing jobs because of symptoms would lower the prevalence of health problems in the work force and tend to attenuate dose-response associations.…”
Section: Respiratory Diseasementioning
confidence: 99%
“…21,22 ). A clear obstructive pattern of pulmonary ventilation parameters was repeatedly found in aluminium potroom workers 20,[23][24][25] . Radiographic findings may vary considerably, showing nodular or slightly irregular opacities that may merge into more prominent formations, most frequently in the upper lung fields 15,16,21,26 .…”
Section: Review Of Knowledge On Pulmonary Aluminosis Essential Studiesmentioning
confidence: 79%
“…Crepitation is also reported 16 . Restrictive ventilatory defects are observed, sometimes accompanied by decreased diffusing capacity 12,15,18,20 . On the other hand, Townsend et al reported a relationship of impaired lung function to a higher prevalence of small opacities and a decrease in FEV 1 in workers with increasing duration and cumulative total dust exposure (in one study exposure of 20 or more years) (ref.…”
Section: Review Of Knowledge On Pulmonary Aluminosis Essential Studiesmentioning
confidence: 99%